Relationship between caries experience and body mass index among 5-15 year old schoolchildren of Piparia Village, Vadodara District, Gujarat - C G Ajithkrishnan; K Thanveer; Hemal R Patel (Wolters Kluwer Medknow Publications, 2013)
Aim: To assess the relationship between caries experience and body mass index among 5-15 year old schoolchildren of Piparia High school, Piparia Vadodara district, Guj arat. Materials & Method: Across sectional study was conducted among 167,5-15 year old school children of Piparia High school, Piparia, Vadodara district, Gujarat. To detect caries, WHO modified DMFT/dft index was used. The body mass index (BMI = body weight / body height2 (kg/m2) was used to determine weight category. Data was analyzed by SPSS version 14. Tukey's Post Hoc test at 5% level of significance was applied to compare statistically significant difference in BMI & DMFT/dft values. Results: Out of 167 study subjects, 5 (3 %) were having primary dentition, 57 (34.1%) with mixed dentition and 105 (62.9%) with permanent dentition. There was no statistically significant difference in the mean DMFT/dft values among subjects with different BMI categories. (p=0.477, 0.792 & 0.879 for DMFT andiM).757 & 0.102 for dft). Conclusions: There was no association between BMI and DMFT/dft values. As a part of health care team, dentist and dental students should be exposed to the changing demographics and sequel of obesity in children.